IMPROVEMENT OF SLEEP QUALITY THROUGH PROGRESSIVE RELAXATION IN ELDERLY IN THE SEMPAJA PUSKESMAS AREA - Bachtiar Safrudin Lubis; Milkhatun Milkhatun (Jurnal Ilmu Kesehatan, 2020)
Decreasing physical, psychological and social functions will have an impact on the overall sleep phase of the elderly. An imperfect sleep cycle can cause the elderly not to sleep soundly, often wake up and the total amount of sleep per day will decrease. Nurses can solve these problems with several nursing interventions through progressive relaxation and healthy sleep. The aim of the study was to see the effect of progressive relaxation and healthy sleep on decreasing sleep disturbances in the elderly group. This research uses a quasi experiment design with a pre-post test without control approach. Measurement of sleep quality of the elderly using the Pittsburgh Sleep Quality Index (PSQI) instrument. This analysis uses univariate and bivariate analysis. Bivariate analysis using paired t-test. Analysis of bivariate Wilcoxon correlation data, obtained score correlation coefficient questionnaire about knowledge between (pretest) and after (posttest) given treatment in the form of progressive relaxation of 0,000 with sig numbers or p-value = 0,000> 0.05 or significant.